An investigation into non-suicidal self-injury and its influencing factors among middle school students in a city in Hebei province - Yanan Liu; Na Li; Yafan Li; Meng Wang; Yongliang Wang; Yanan Chen; Ling Hang; Jianan Ling; Wenting Lu; Minglong Gao (Frontiers in Public Health)
ObjectiveTo investigate the incidence and influencing factors of non-suicidal self-injury (NSSI) among middle school students in a city within Hebei Province.MethodsA total of 11,321 students from grades one to three from two middle schools in Dingzhou, Hebei Province, were randomly selected. Socio-demographic data, mental disorders, coping styles, and experiences of childhood abuse were collected.Results10,982 students finally included in the statistical analysis. We found that the detection rate of NSSI in the past year was 11.6%. Comparatively, the NSSI group and the non-NSSI group revealed significant discrepancies in coping styles, childhood abuse, and mental disorders. Factors protective against NSSI included living with parents, a problem-oriented coping style, and a preference for participating in extracurricular activities (OR = 0.729, 0.966, 0.815). NSSI's risk factors included frequent parental quarrels, interpersonal tension and sensitivity, depression, emotion-oriented coping styles, and childhood emotional abuse (OR = 1.322, 1.045, 1.141, 1.023, 1.137).ConclusionThe detection rate of NSSI within the past year in the city of Hebei stands at 11.6%. Considering the recognized risk and protective factors for NSSI, the possibility of NSSI may be decreased through the promotion of a harmonious home environment, encouraging positive emotional interaction, and the facilitation of greater involvement in extracurricular activities.